Screening of bacteriocin-producing dairy Enterococcus strains using low-cost culture media - Garmasheva, Inna L.; Oleschenko, Ljubov T. (Frontiers in Microbiology, 2023)
This study was carried out to select the bacteriocinogenic strains among Enterococcus strains isolated from Ukrainian traditional dairy products using a low-cost media for screening, that containing molasses and steep corn liquor. A total of four hundred seventy-five Enterococcus spp. strains were screened for antagonistic activity against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, and Listeria monocytogenes indicator strains. The initial screening revealed that 34 Enterococcus strains during growth in low-cost medium containing corn steep liquor, peptone, yeast extract, and sucrose produced metabolites with inhibition activity against at least of the indicator strains used. Enterocin genes entA, entP, and entB were detected in five Enterococcus strains by PCR assay. Genes of enterocins A and P were found in E. faecalis 58 and Enterococcus sp. 226 strains, enterocins B and P – in Enterococcus sp. 423, enterocin A – in E. faecalis 888 and E. durans 248 strains. Bacteriocin-like inhibitory substances (BLIS) produced by these Enterococcus strains were thermostable and sensitive to proteolytic enzymes. To our knowledge, this is the first report on the isolation of enterocin-producing wild Enterococcus strains from traditional Ukrainian dairy products using a low-cost media for screening bacteriocinogenic strains. Strains E. faecalis 58, Enterococcus sp. 423, and Enterococcus sp. 226 are promising candidates for practical use as producers of bacteriocins with inhibitory activity against L. monocytogenes using molasses and steep corn liquor as cheap sources of carbon and nitrogen, that can significantly reduce the cost of industrial bacteriocin production. Further studies will be required to determine the dynamic of bacteriocin production, its structure, and mechanisms of antibacterial action.